Language Competence and Its Influence on Understanding English Literature - Jauhari, Iman; FIkri, Moh Hilman; Partini, Partini (Jurnal Pembelajaran dan Riset Pendidikan, 2021)
Language competence plays a vital role in the comprehension and interpretation of English literature. This study explores the relationship between linguistic proficiency and the ability to understand literary texts, focusing on how mastery of language structures, vocabulary, and contextual knowledge influences the interpretation of themes, narratives, and stylistic elements. English literature, with its diverse genres and complex expressions, often requires a high level of linguistic skill to fully grasp its depth and nuances.The research adopts a mixed-method approach, combining qualitative and quantitative analyses. Data were collected through assessments of linguistic proficiency and literature comprehension among students at different language competency levels. Findings indicate a strong correlation between language competence and the ability to understand and appreciate literary works. Students with advanced language skills demonstrated higher capabilities in interpreting symbolism, analyzing literary devices, and understanding cultural and historical contexts. This study highlights the importance of integrating language development with literature education to enhance students' literary competence. The results provide valuable insights for educators and curriculum developers in designing effective pedagogical strategies that address linguistic gaps and promote a deeper engagement with English literature